Estudos biossistemáticos em espécies do gênero Hypnea J.V. Lamouroux (Gigartinales, Rhodophyta) - Jesus, Priscila Barreto de (2016)
The genus Hypnea presents erect or prostrate thallus, abundantly and irregularly branched (dichotomously or laterally branched), with several short branchlets. Currently, the genus has 66 species widely distributed in tropical and subtropical waters, occurring in the Atlantic, Indian and Pacific Oceans. However, taxonomic problems are recurrent in the genus, with a large number of taxonomic complexes, poorly defined and cryptic species, probable synonyms and frequent failure to identify some species. In view of these difficulties, this study aimed to conduct biosystematic and phylogenetic studies in the genus Hypnea, based on morphological, ecological and molecular characters (COI-5P, rbcL and psaA). In this study, H. stellulifera was referred to the Atlantic Ocean for the first time. Our results indicate that the limits of intra- and interspecific molecular divergence levels in Hypnea species should be reconsidered, especially in cosmopolitan taxa. Several DNA-based delimitation methods (mBGD, ABGD, SPN, PTP, GMYCs and GMYCm) were carried out in order to delimit the H. cervicornis complex. These analyzes indicate the existence of a new specie to science, widely distributed on the Brazilian coast, described here as H. brasiliensis. We propose that H. aspera and H. flexicaulis represent synonyms of H. cervicornis. Recently, Brazilian specimens identified as H. musciformis, H. nigrescens and H. valentiae were considered morphological variations of H. pseudomusciformis. We investigated the phenology of a tropical population of “Hypnea nigrescens” in order to describe its biology and verify if this ecological approach would be helpful to elucidate its taxonomic status. Biomass, thallus length and reproductive stage were estimated over the period of a year. "H. nigrescens" showed remarkable ecological differences from "H. musciformis”. High frequency of female and male gametophytes indicated that this approach can be an important taxonomic marker. The evolutionary history of H. musciformis and H. pseudomusciformis were investigated based in a phylogeographic approach. Results confirmed the differentiation between H. musciformis and H. pseudomusciformis populations, indicating that the first specie is in equilibrium, while the second diverged more recently and is expanding. We confirmed the extension of the distribution range of H. pseudomusciformis from South America to Africa, while H. musciformis seems to be restricted to the Northern Hemisphere. These findings suggest vicariance as the main speciation pattern. Combined analysis of three molecular markers, as well as the large number of sequences analyzed (255 from 28 species), resulted on the more robust and well-resolved phylogeny of the genus to date. Our analyses proved that the three sections currently recognized of the genus Hypnea are invalid, since they all appeared as paraphyletic or polyphyletic. Taxonomic problems remain in those clades with cryptic species and in those in which the reproductive isolation seems to be incomplete. Our data demonstrated the complexity and importance of biosystematic studies for the delimitation of species limits and a better understanding of evolutionary relationships in Hypnea.